How Does AI Improve Detection of Lung Nodules on Chest X-rays? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2018)
Lung cancer remains a leading cause of cancer-related mortality worldwide, with late-stage diagnosis contributing significantly to poor patient outcomes. Ear...
Keywords: AI in Medical Imaging and Diagnostics; Improve; Detection; Nodules; Artificial Intelligence; Deep Learning; Healthcare